2022
DOI: 10.12928/telkomnika.v20i6.21783
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of mango fruit pest and disease recognition

Abstract: Mango is a popular fruit for local consumption and export commodity. Currently, Indonesian mango export at 37.8 M accounted for 0.115% of world consumption. Pest and disease are the common enemies of mango that degrade the quality of mango yield. Specialized treatment in export destinations such as gamma-ray in Australia, or hot water treatment in Korea, demands pest-free and high-quality products. Artificial intelligence helps to improve mango pest and disease control. This paper compares the deep learning mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…VGG16 is a model developed by the Vision Geometry Group at Oxford University [15]. This model managed to win the Imagenet competition in 2014 [9]. The VGG16 architecture consists of a series of uniform convolution blocks followed by an integrated pooling layer.…”
Section: Vgg16 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…VGG16 is a model developed by the Vision Geometry Group at Oxford University [15]. This model managed to win the Imagenet competition in 2014 [9]. The VGG16 architecture consists of a series of uniform convolution blocks followed by an integrated pooling layer.…”
Section: Vgg16 Modelmentioning
confidence: 99%
“…one of them is in research conducted by Samala, et al by identifying diseases in tomato leaves using InceptionV3 architecture which produces an accuracy rate of 99% [8]. His further research was conducted by Kusrini, et diseases in mangoes, it was found that the accuracy results using the VVG16 model achieved top validation with accuracy of 89% and 90% respectively [9]. Another study conducted by Tsabitah Ayu, et al using a model (CNN) to classify the types of mango leaves affected by pests and healthy obtained accuracy results of 0.96% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Sementara pelatihan dilakukan untuk melatih lapisan yang terakhir (Fully Connected Layer) dengan fungsi softmax. Dengan membatasi bobot untuk lapisan terakhir jaringan, kami dapat mempercepat waktu pelatihan tanpa mengorbankan akurasi pengklasifikasi [17]. Pembekuan bobot tersebut dinamankan Fine-tuning.…”
Section: Model Klasifikasiunclassified